Seasonal scenario planning for matching seed supply and demand: MS Excel decision support tool - Steinke, Jonathan; Ortíz Crespo, Berta (2022)
This is an MS Excel tool for seasonal scenario planning. This tool correlates historical seasonal rainfall with seed sales. Using expected rainfall forecasts the tool gives an estimate of expected seed seales in the coming season. The tool should be introduced to decsion makers in a workshop, presented jointly with "seasonal scenario planning: worshop format" and "seasonal scenario planning: workshop slides".